2001
DOI: 10.1037/1076-898x.7.3.207
|View full text |Cite
|
Sign up to set email alerts
|

Matching identities of familiar and unfamiliar faces caught on CCTV images.

Abstract: People can be inaccurate at matching unfamiliar faces shown in high-quality video images, even when viewpoint and facial expressions are closely matched. However, identification of highly familiar faces appears good, even when video quality is poor. Experiment 1 reported a direct comparison between familiar and unfamiliar faces. Participants who were personally familiar with target items appearing on video were highly accurate at a verification task. Unfamiliar participants doing the same task performed very i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
307
3
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 313 publications
(339 citation statements)
references
References 20 publications
27
307
3
2
Order By: Relevance
“…If face recognition can be understood as matching an image to a stored representation, then matching two images of an unfamiliar face will essentially be an image-matching (rather than a face-matching) task. Bruce et al, (1999Bruce et al, ( , 2001 and Hancock et al (2000) suggest that this is exactly the strategy used in unfamiliar face matching, in contrast to a more abstractive approach in which some canonical knowledge of face variation is recruited. In order to become an expert with a familiar face, and be able to recognise it over an increasing range of visual conditions, one simply needs to improve one's representation.…”
Section: Discussionmentioning
confidence: 99%
“…If face recognition can be understood as matching an image to a stored representation, then matching two images of an unfamiliar face will essentially be an image-matching (rather than a face-matching) task. Bruce et al, (1999Bruce et al, ( , 2001 and Hancock et al (2000) suggest that this is exactly the strategy used in unfamiliar face matching, in contrast to a more abstractive approach in which some canonical knowledge of face variation is recruited. In order to become an expert with a familiar face, and be able to recognise it over an increasing range of visual conditions, one simply needs to improve one's representation.…”
Section: Discussionmentioning
confidence: 99%
“…Bruce et al, 1999Bruce et al, , 2001Clutterbuck & Johnston, 2002;Megreya & Burton, 2006). However, when these studies are extended to include live matches, equivalently poor performance is seen.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely established that, while identification of familiar faces from CCTV footage is highly reliable and accurate (Burton, 2013; Burton, Wilson, Cowan & Bruce, 1999), the task of identifying or even matching unfamiliar faces is characterised by a high rate of error (Bruce et al, 1999; Bruce, Henderson, Newman & Burton, 2001; Burton et al, 1999). Indeed, Burton et al (1999) demonstrated that the recognition of familiar faces, even from poor‐quality CCTV, is fast and effortless.…”
mentioning
confidence: 99%